Antifeeding Activity of Several Plant Extracts Against Lymantria dispar L. (Lepidoptera: Lymantriidae) Larvae - Gvozdenac, Sonja M; Inđić, Dušanka V; Vuković, Slavica M; Grahovac, Mila S; Tanasković, Snežana T (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2013)
Lymantria dispar L. is the most devastating polyphagous pest of deciduous forests, orchards and urban greenery. To prevent damages that L. dispar larvae cause in forestry, agriculture and horticulture, mechanical measures and the use of biological insecticides are the most frequently applied practices. However, the use of conventional insecticides is inevitable in crop protection and forest management on smaller areas, especially in gradation years. However, inadequate use of these chemicals has led to disturbance of biocoenotic balance, outbreaks of some previously less harmful organisms and pesticide residues in soil and watercourses in some regions. To mitigate these consequences it is necessary to harmonize L. dispar control with integrated management principles by applying selective and less toxic insecticides. Therefore, the potential of botanical insecticides and antifeeding substances is gaining in importance. The aim of this study was to assess the influence of ethanol extracts (1, 2 and 5%) of Ambrosia artemisiifolia L., Erigeron canadensis L., Daucus carota L., Morus alba L. and Aesculus hippocastanum L. on the feeding intensity of L. dispar larvae, i.e. to evaluate their antifeeding activity under the conditions of “no-choice” test. Ten larvae per repetition were placed in Petri dishes and offered oak leaf slices (2 x 9 cm2/repetition) previously dipped in plant extract or ethanol (1, 2, and 5%) for the control. Feeding intensity, expressed as a percentage of consumed leaf area (%), was measured after 48 h. For assessing the antifeeding activity of plant extracts AFI was calculated and the extracts were classified according to scale: no antifeeding activity, slight antifeeding activity, moderate antifeeding activity and strong antifeeding activity. Data were analyzed using a two-way ANOVA and Duncan`s multiple range test. The results indicate that plant species, i.e. the origin of extracts, had a significant influence on the feeding intensity of L. dispar larvae, while concentration and interaction (plant species x concentration) were not factors of influence. Ae. hippocastanum and M. alba extracts significantly reduced the consumed leaf area (6.24, 18.93%, respectively), compared to the control (97.59%), while the extract of D. carota had a phagostimulative effect (98.88%). Based on AFI values, Ae. hippocastanum extract (87.10-89.05%) had a strong antifeeding activity, and M. alba medium-to-strong (64.33-71.37%).
Keywords: Plant extracts; Gypsy moth; Insecticides; Antifeedants